Mengintegrasikan Pendidikan Akademik dan Pelatihan Kerja Menuju Kesiapan Kerja Lulusan Program Studi Pendidikan Agama Islam STIT Raden Wijaya Mojokerto Menyongsong Era Industri 4.0 - Achmad Padi (PROGRESSA: Journal of Islamic Religious Instruction, 2019)
The heated discussion and debate about university disruptions triggered by the recent Jim Clifton article, "University: The Impending Disruption" in social media outlines questions and concerns about the future role of higher education in supplying industrial labor in the world. The trigger is Google and Ernst & Young ads will pay anyone who is able to work with him without having to have a diploma, including a diploma from a university. It's like lightning in broad daylight, surprising and reaching a position that has been enjoyed by universities in the world which in fact are suppliers of expertise, results of research, and thoughts needed by the industrial world. however, it seems that it has been canceled by Google and Ernst & Young, which soon followed other giant global companies. The college death bell was stretched by two giant companies, following an article written by Terry Eagleton, entitled "University Slow Death". Then the question is how does the STIT Islamic Education Study Program Raden Wijaya Mojokerto integrate academic education and job training towards graduate work readiness to meet the Industrial Age 4.0 ?. The results of the discussion concluded: The STIT Raden Wijaya Mojokerto Islamic Education Study Program in integrating academic education and job training towards graduate work readiness to meet the Industrial Age 4.0 must integrate the following dual tracks: 1) make alumni achieve professional talent from three qualification levels (skilled, expert and degree) because every job needs to learn practices that are embedded in a dual structure of education and training programs which essentially understand theory and master practice. Therefore, the content of practice needs to regulate the elements of training in each subject; 2) To obtain the ability to complete professional assignments fully expressed more precisely by the idea of ??holistic problem solving by playing an objective situation scenario for students competing with each other in high functionality and low cost.